Correction: A diffusion tensor-based method facilitating volumetric assessment of fiber orientations in skeletal muscle. - Laura Secondulfo; Melissa T Hooijmans; Jozef J M Suskens; Valentina Mazzoli; Mario Maas; Johannes L Tol; Aart J Nederveen; Gustav J Strijkers (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0261777.].